Optimization of operating parameters of novel composite adsorbent for organic pollutants removal from POME using response surface methodology - Adeleke, A.O.; Ab. Latiff, Ab Aziz; Al-Gheethi, A.A.; Daud, Zawawi (Elsevier, 2017)
The present work aimed to develop a novel composite material made up of activated cow bone powder (CBP) as a starting material for reducing chemical oxygen demand (COD) and ammonia-nitrogen (NH3eN) from palm oil mill effluent (POME). The optimization of the reduction efficiency was investigated using response surface methodology (RSM). Six independent variables used in the optimization experiments include pH (4e10), speed (0.27e9.66 rcf), contact time (2e24 h), particle size (1e4.35 mm), dilution factor (100e500) and adsorbent dosage (65e125 g/L). The chemical functional groups were determined using Fourier transform irradiation (FTIR). The elemental composition were detected using SEM-EDX, while thermal decomposition was investigated using thermo gravimetric analysis (TGA) in order to determine the effects of carbonization temperature on the adsorbent. The results revealed that the optimal reduction of COD and NH3eN from raw POME was observed at pH 10, 50 rpm, within 2 h and 3 mm of particle size as well as at dilution factor of 500 and 125 g L1 of adsorbent dosage, the observed and predicted reduction were 89.60 vs. 85.01 and 75.61 vs. 74.04%, respectively for COD and NH3eN. The main functional groups in the adsorbent were OH, NeH, C]O, C]C, CeOeC, CeOeH, and CH. The SEMEDX analysis revealed that the CBP-composite has a smooth surface with high contents of carbon. The activated CBP has very stable temperature profile with no significant weight loss (9.85%). In conclusion, the CBP-composite investigated here has characteristics high potential for the remediation of COD and NH3eN from raw POME.